2019
DOI: 10.1039/c8sm02103a
|View full text |Cite
|
Sign up to set email alerts
|

Active transport in a channel: stabilisation by flow or thermodynamics

Abstract: Recent experiments on active materials, such as dense bacterial suspensions and microtubulekinesin motor mixtures, show a promising potential for achieving self-sustained flows. However, to develop active microfluidics it is necessary to understand the behaviour of active systems confined to channels. Therefore here we use continuum simulations to investigate the behaviour of active fluids in a two-dimensional channel. Motivated by the fact that most experimental systems show no ordering in the absence of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 45 publications
(67 reference statements)
5
34
0
Order By: Relevance
“…A complex interface with a persistent saptio-temporal structure (panel C) is observed for a range of activities beyond the instability. At even higher activities the interface cannot be sustained, as the isotropic phase in the channel becomes unstable, and complex flow states, danc-ing D and active turbulence E, are observed in line with earlier reports 4,48 .…”
Section: Flow States and Interfacial Instabilitysupporting
confidence: 91%
“…A complex interface with a persistent saptio-temporal structure (panel C) is observed for a range of activities beyond the instability. At even higher activities the interface cannot be sustained, as the isotropic phase in the channel becomes unstable, and complex flow states, danc-ing D and active turbulence E, are observed in line with earlier reports 4,48 .…”
Section: Flow States and Interfacial Instabilitysupporting
confidence: 91%
“…First, we consider the case of a positive flow-aligning parameter in the flow-aligning regime with λ = 0.7 (ν = 1.2). Since most of the numerical studies so far have only focused on extensile activities [16,23,25,30,[58][59][60][61][62], we begin by exploring the effect of contractile activity to shed light on possible different patterns. At low contractile activities, splay instabilities are followed by the unbinding of ±1/2 defect pairs, and active turbulence is established, a process that is consistent with both previous theoretical predictions [17,25] and numerical simulations [63,64].…”
mentioning
confidence: 99%
“…Finally, a logical next step towards predictive modeling of the biomechanical and biophysical aspects of swarming will be to combine agent-based microscopic models as in this paper with mesoscale models for active liquid crystals [32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent numerical and theoretical studies have focused on the collective flows and identified dynamical exponents characterizing the energy spectrum and spatiotemporal features as well as variations near interfaces 24,28 . To explain these features, theoretical models for swarming systems based on adaptations of classical nematic hydrodynamic theories and hydrodynamic multiphase models have been used to characterize the phase-separating active nematic and passive phases and propagation of interfaces of active nematics on substrates [33][34][35][36] . Understanding the role of swarming in enabling bacterial collective motility and rapid propagation is both important and timely; this will require combination of experimental, analytical and computational approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation